Organizational de-structuring? Latour's potential contribution to the critical realist – pragmatist dispute. Issue 3 (27th May 2022) - Kemp, Stephen
ABSTRACT: This article explores a key difference that Elder-Vass has identified between critical realism and pragmatism: their divergent views on the viability of the concept of social structure. Noting that this is also a point of dispute between critical realists and Actor-Network Theorists, I try to contribute to the debate about social structure by focusing on the question of whether organizations are structures, drawing on the views of a pragmatist-leaning ANT - Bruno Latour - to evaluate those of a critical realist - Dave Elder-Vass. I suggest that Latour's arguments can be used to identify two challenges for Elder-Vass's approach, questioning both whether an organization has a singular structural form and whether organizations have determinable powers and impacts. I then consider whether Latour's approach is vulnerable to critical realist arguments that perspectives which deny the existence of social structure cannot account for long-term stabilities, fail to connect different cases, and are individualistic in character.